MESSAGE FROM THE EDITIOR-IN-CHIEF - Datuk Prof. Dr. Hjh. Bibi Florina Abdullah, (The Malaysian Journal of Nursing (MJN), 2020)
The world is confronted with unknown challenges due to the present global pandemic. Increasing worries regarding the stress on health care systems worldwide are already on going and is expected to get significantly worse. This health crisis adversely effects not only frontline staff and clinical leaders but all systems and communities. COVID-19 has also already interrupted the workflow of universities and academic institutions. Within the health field, nursing schools are facing challenges related to the development of the next generation of care providers. As a result, there are various apprehensions and concerns of nursing educators and nursing students related to the the COVID-19 pandemic. In spite, of all the fear and anxiety, there are lessons in hope. Students nurses all over the world have given priority to health of patients and communities. Students even in this crisis actively share insightful, is eloquent, and provide honest thoughts on the impact of this pandemic worldwide. Even without direct clinical education, these nursing students are learning about the role of the nurse in a wider perspective. Their responses have been a salve in this petrifying situation. Their intelligence and compassion are one of the factors that guide us through this emergency. We have also perceived the dedication, roles, and noteworthy contributions that nurses play in the health care system. Moreover, the students entering the academic programs in the future, will be able to begin their education being alert of risks and challenges that no other cohort could have ever imagined. We all know that COVID-19 is an enduring crisis. This situation has brought to us real-time lesson in equity, social righteousness, guidance, ethics, and patient care. This pandemic will forever shift the educational landscape in a new direction. The Malaysian Journal of Nursing in the present issues also reflect the ever-enduring nature of nurses in this predicament. The journal focuses on providing psychological support to nurses and suggest coping strategies to decrease the present stress level. In this manner nursing students will be aware of the present public health emergency response and disease surveillance, so that they are able to keep themselves and their patients safe.